The Effect of Capital Expenditure, Labor, and Inflation on Economic Growth in Makassar City - Elisabeth, Cherly (Golden Ratio of Social Science and Education, 2023)
This study aims to determine the effect of capital expenditure on economic growth in Makassar City, the effect of labor on economic growth in Makassar City and the effect of inflation on economic growth in Makassar City. The research hypothesis uses a theory / concept base, supported by previous studies that have similar variables. This research was conducted in Makassar City. The type of data used is secondary data. The data analyzed in this study for 11 years. Using descriptive statistical techniques, Classical Assumption Test and multiple linear regression assisted by Eviews 10.0 for data analysis. The results showed that Capital Expenditure has a positive and significant effect on Economic Growth in Makassar City, Labor has a positive and insignificant effect on Economic Growth in Makassar City. Inflation has a negative and insignificant effect on economic growth in Makassar city.